Spirit Moderasi dalam Kajian Ilmu Falak - Muhammad Qorib; Muhammad Hidayat (University of Muhammadiyah Sumatera Utara, 2022)
There are several different views and decisions on the issue of Astrology, including first, the difference in the start of the morning prayer, second, the difference in determining the beginning of the month, and third, regarding the Qibla direction. In responding to these differences, in the matter of Astrology one must be able to put forward the spirit of Moderation which aims to maintain harmony, peace and unity in order to be able to deal with other, more complex problems. This study uses a quantitative approach which originates from OIF UMSU field data and is qualitative which originates from various literature. The results of this study show that the Spirit of Moderation is the key in responding to different views and decisions on the issue of Astrology in Indonesia.